Exploring The Physiological Aspect Of Hridaya In Ayurved - Dr. Ruchiben Ashvinbhai Hedapara, Dr. Sandeep Kumar, Dr. Sachin Deva, Dr. Sunil Khandare (International Journal of Modern Agriculture, 2021)
In Ayurvedic texts 107 number of Marmas(vital organs) are mentioned, while Trimarmasi.eBasti(Urinary System), Hridayam(Heart) and Shira (Head) are considered supreme among themselves, because they possess Pran (Life force) in them.1 Among these Trimarmas,Hridayahas its own importance as this is the seat of Chetna. AcharyaCharakexplained aboutDashpranayatan(Ten Principal seatsof life) in which the Prana are established and the Hridaya is one of the Dashpranayatan.2According to Ayurved it is a site of Mana (Mind) and is the Mula of Manovahi Srotas3 and thus related with our thought process and emotions. Rasa Dhatuis essential for Preenan (Nourishment)4and Hridaya is considered as the Mula (origin source) of Rasavaha Srotas5 through which Rasa circulates all over the body and provide nourishment.Similarly Mula of PranavahaSrotas is also explained as Hridaya.5TheHridayais the supreme location ofOjas(Essence of all Dhatus)and locus of consciousness is the reason why physicians call it Hridaya, Mahator Artha.6. The present review critically examines the available literatures to evaluate the physiological aspect of Hridayain Ayurved.